DHLCA Alleviates Diabetic Kidney Disease via TGR5/FXR Activation and Gut Microbiota Remodeling - Zhou H; Mu X; Hu H; Zhao S; Hu N; Yang M; Jiang J (Drug Design, Development and Therapy)
Hua Zhou,1,* Xiaodie Mu,2,* Huiyue Hu,1,* Shuya Zhao,1 Nan Hu,3 Min Yang,1,* Jingting Jiang4– 6,* 1Department of Nephrology, The Third Affiliated Hospital of Soochow University, Changzhou, 213003, People’s Republic of China; 2Department of Nephrology, The Second People’s Hospital of Hefei, Hefei, 230011, People’s Republic of China; 3Department of Pharmacy, The Third Affiliated Hospital of Soochow University, Changzhou, 213003, People’s Republic of China; 4Department of Tumor Biological Treatment, The Third Affiliated Hospital of Soochow University, Changzhou, 213003, People’s Republic of China; 5Jiangsu Engineering Research Center for Tumor Immunotherapy, The Third Affiliated Hospital of Soochow University, Changzhou, 213003, People’s Republic of China; 6Institute of Cell Therapy, The Third Affiliated Hospital of Soochow University, Changzhou, 213003, People’s Republic of China*These authors contributed equally to this workCorrespondence: Jingting Jiang, Department of Tumor Biological Treatment, Jiangsu Engineering Research Center for Tumor Immunotherapy, Institute of Cell Therapy, The Third Affiliated Hospital of Soochow University, Changzhou, People’s Republic of China, Email jiangjingting@suda.edu.cn Min Yang, Department of Nephrology, The Third Affiliated Hospital of Soochow University, Changzhou, People’s Republic of China, Email yangmin1516@suda.edu.cnPurpose: Diabetic kidney disease (DKD) is a major contributor to chronic kidney disease worldwide. Bile acids (BAs) are increasingly recognized as key regulators of glucose metabolism and kidney function. This study aimed to investigate the role of BA metabolism in the progression of DKD.Methods: Plasma BA profiles were measured in healthy controls (HC), patients with type 2 diabetes mellitus (T2DM), and patients with DKD using ultra-high-performance liquid chromatography–tandem mass spectrometry (UPLC-MS/MS). After identifying potential BA biomarkers in the clinical cohort, in vivo validation was conducted using dehydrolithocholic acid (DHLCA) intervention in DKD mouse model. Kidney injury markers, as well as the expression of Takeda G protein-coupled receptor 5 (TGR5) and farnesoid X receptor (FXR), were evaluated. In addition, gut microbiota (GM) composition was analyzed via metagenomic sequencing following DHLCA treatment.Results: The plasma DHLCA levels were significantly lower in DKD with macroalbuminuria group compared to T2DM group and DKD with microalbuminuria group (P < 0.01). Partial Spearman correlation analysis adjusted for age and diabetes duration showed that DHLCA levels were negatively correlated with urine albumin (ρ = – 0.347; 95% CI, – 0.531 to – 0.135; q = 0.008) and urine albumin-to-creatinine ratio (UACR) (ρ = – 0.332; 95% CI, – 0.499 to – 0.155; q = 0.010). In vivo, DHLCA administration significantly reduced UACR and fasting blood glucose (FBG) levels (P < 0.01), and improved liver function (ALT, P < 0.05) in DKD mice. DHLCA treatment attenuated renal tubular injury, restored TGR5 and FXR expression in kidney tissue, and decreased levels of kidney injury molecule-1 (KIM-1) and neutrophil gelatinase-associated lipocalin (NGAL). Metagenomic analysis revealed an enrichment of Lachnospiraceae bacterium following DHLCA treatment.Conclusion: DHLCA may represent a promising therapeutic candidate for DKD by targeting the TGR5/FXR signaling pathway and GM remodeling. Its metabolic and kidney benefits, along with an improved hepatic profile and absence of hepatotoxicity, support further translational investigation. Keywords: bile acid, diabetic kidney disease, farnesoid X receptor, gut microbiota, Takeda G protein-coupled receptor 5